Are international travelers from Portugal aware of malaria? Pre-travel assessment between 2019-2020. (30th September 2020) - Malcata, F; Faria, B; Saldanha, G; Antunes, D
Abstract: Background: Malaria is the main cause of death by infection among travelers. It may be prevented via chemoprophylaxis and personal protection. In 2017, European Centre for Disease Prevention and Control reported 8401 cases in Europe-8023 imported (99, 8% travel-related). Misperception of the risk and inadequate pre-travel preparation are some of the reasons for these case numbers. The main goal of this study was to assess travelers' knowledge of malaria to improve medical advice in pre-travel consultations in the Oporto international vaccination centre (OIVC), minimizing the risk among travelers going to malaria endemic regions. Methods: Before their pre-travel consultation in OIVC, 452 travelers filled the questionnaire with demographic issues, journey characteristics and answers about malaria's etiology, prevention and treatment. All travelers signed an informed consent form. Data were collected between July 2019 and January 2020 and analyzed via descriptive statistics and hypothesis test for comparing two populations proportions for each question. Results: 40, 4% of travelers age was 26 - 35 years; 52, 3% were female; and 67, 5% of the planned trips were 1-3 week-long, mainly for tourism (n = 285). For most of malaria questions, travelers holding a university degree (n = 352) exhibited a statistically significant difference (p < 0, 005) in knowledge with an average of 70, 5% correct answers compared to 58.5% of those with lower education level. However, regarding previous pre-travel appointments: for the majority of questions knowledge was similar (p > 0, 005) comparing to those who had first pre-travel consultation (n = 287), with an average of correct answers of 73, 7% and 65, 5%, respectively. Conclusions: A stronger focus on malaria in pre-travel medical advice is necessary to increase travelers' knowledge. It is also essential to adapt malaria information to travelers' characteristics- in view of the lower percentage of correct answers by those with a lower education level. Key messages: Malaria is a potential health risk for international travellers and an important cause of death among them. This may be caused by inaccurate perception of risk and sub-optimal pre-travel preparation. This study is the largest in Portugal to assess traveleŕs knowledge about malaria. It is crucial in order to improve medical advice and minimize the risk.